A Review of Synthetic Access to Therapeutic Compounds Extracted from Psilocybe - Raphaël Serreau; Ammar Amirouche; Amine Benyamina; Sabine Berteina-Raboin (MDPI AG, 2022)
Psychedelics are used for various pathologies of the central nervous system and are currently the subject of much research, some of which relates to the compounds contained in various Psilocybe-type hallucinogenic mushrooms. It is difficult, however, to obtain and purify sufficient quantities of these compounds from fungi to carry out biological studies, hence the need to develop simple and efficient synthetic routes. We review here the various syntheses used to obtain these molecules, focusing first on the classic historical syntheses, then the use of more recent metallo-catalyzed couplings and finally the known biocatalytic methods for obtaining these molecules. Other access routes are certainly possible and should be the subject of future research given the therapeutic interest of these compounds.